2020
DOI: 10.1038/s41467-020-18063-x
|View full text |Cite
|
Sign up to set email alerts
|

High force catch bond mechanism of bacterial adhesion in the human gut

Abstract: Bacterial colonization of the human intestine requires firm adhesion of bacteria to insoluble substrates under hydrodynamic flow. Here we report the molecular mechanism behind an ultrastable protein complex responsible for resisting shear forces and adhering bacteria to cellulose fibers in the human gut. Using single-molecule force spectroscopy (SMFS), singlemolecule FRET (smFRET), and molecular dynamics (MD) simulations, we resolve two binding modes and three unbinding reaction pathways of a mechanically ultr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 83 publications
2
59
0
Order By: Relevance
“…This can be explained by the allosteric properties of FimH whose binding pocket for mannose exists as an inactive lowaffinity state at low stress but switches to a tight high-affinity conformation under tensile load (Le Trong et al, 2010;Rabbani et al, 2018;Sauer et al, 2016;Thomas et al, 2006). Another catch bond involving allosteric regulation has recently been suggested by Liu et al (2020). They unraveled how gut microbes modulate cellular adhesion through mechanically stable Dockerin:Cohesin interactions in bacterial cellulosome protein complexes: at high loading rates (high shear) a domain neighboring the Dockerin domain allosterically inhibits the low-force unbinding pathway of the complex, giving rise to a catch binding mechanism and shear-enhanced bacterial adhesion.…”
Section: Cell Surface Adhesins Strong Players In Pathogenicitymentioning
confidence: 99%
“…This can be explained by the allosteric properties of FimH whose binding pocket for mannose exists as an inactive lowaffinity state at low stress but switches to a tight high-affinity conformation under tensile load (Le Trong et al, 2010;Rabbani et al, 2018;Sauer et al, 2016;Thomas et al, 2006). Another catch bond involving allosteric regulation has recently been suggested by Liu et al (2020). They unraveled how gut microbes modulate cellular adhesion through mechanically stable Dockerin:Cohesin interactions in bacterial cellulosome protein complexes: at high loading rates (high shear) a domain neighboring the Dockerin domain allosterically inhibits the low-force unbinding pathway of the complex, giving rise to a catch binding mechanism and shear-enhanced bacterial adhesion.…”
Section: Cell Surface Adhesins Strong Players In Pathogenicitymentioning
confidence: 99%
“…Polymers with specific structures undergo significant conformational changes, and such conformational changes have been found to be reversible [ 24 , 25 , 26 , 27 ]. In the biological field, combining molecular cell biology with SMFS, the complexity of cell or bacterial adhesion is explored to clarify the mechanism by which cell signaling processes enhance adhesion [ 28 , 29 , 30 , 31 ]. In the field of physical chemistry, the single-chain mechanical behavior of polymers in different environments can be obtained by SMFS to explore the interactions between single polymer chains and the surrounding environment [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the same lines, our previous study also observed high amount of proteins on the edges of clay minerals and some absorbed in the cracks upon observing images taken from Atomic Force Microscopy (Math et al 2019 ). AFM, a powerful tool used for single-molecule interaction between protein-ligand (Sumbul and Rico 2019 ), clay minerals-protein (Math et al 2019 ), affinity under in-vitro conditions and protein-substrates like cellulose (Liu et al 2020 ). Also, rupture forces of cellulose binding module and fiber substrates of cellulose, were measured using AFM (Griffo et al 2019 ), and an adhesive force were successfully measured between pesticide degrading enzyme-soil particles (Islam et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of structure of biomolecules like protein helps in studying protein-protein, protein-substrate and protein-fiber interactions (Moro et al 2016 ; Liu et al 2020 ; Moro et al 2020 ). The amino acid (aa) sequence of a protein, the so-called primary structure, can be easily determined from the sequence on the gene that codes for it.…”
Section: Introductionmentioning
confidence: 99%